1986
DOI: 10.1200/jco.1986.4.9.1392
|View full text |Cite
|
Sign up to set email alerts
|

Reduced ability to clear ultrafilterable platinum with repeated courses of cisplatin.

Abstract: Ultrafilterable plasma and urinary levels of platinum were quantitated for 24 hours after the first- and fourth-course infusion of cisplatin (CDDP) to seven patients. Four patients received 80 mg/m2 and three patients received 100 mg/m2 CDDP as a 2-hour infusion. The area under the curve (AUC) of ultrafilterable platinum, average renal clearance (CIR) of ultrafilterable platinum, and percentage of the platinum dose excreted in urine (% E) were determined for each infusion over the 26-hour period of the study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

1987
1987
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 25 publications
1
12
0
1
Order By: Relevance
“…[20] Urinary cisplatin excretion is by glomerular filtration and active renal tubular secretion. [34][35][36] Organic anion and cation transport mechanisms are involved in active renal tubular cisplatin transportP2] Platinum concentrations are higher in the kidney than in plasma or other tissues, particularly in areas of functional and histological damage, i.e. the juxta-medullary region and outer stripe of the medulla.…”
Section: Pathogenesismentioning
confidence: 99%
“…[20] Urinary cisplatin excretion is by glomerular filtration and active renal tubular secretion. [34][35][36] Organic anion and cation transport mechanisms are involved in active renal tubular cisplatin transportP2] Platinum concentrations are higher in the kidney than in plasma or other tissues, particularly in areas of functional and histological damage, i.e. the juxta-medullary region and outer stripe of the medulla.…”
Section: Pathogenesismentioning
confidence: 99%
“…Recently, there have been efforts to develop an optimal therapeutic schedule of chemotherapeutic agents by investigating the pharmacokinetics/pharmacodynamics (PK/PD) correlation (17,18). Reece et al (19) mentioned that repeated courses of CDDP reduced Ccr and increased free Pt AVe. Several investigators also reported that lower Ccr correlated with higher AVC and platelet reduction by CDDP analogs such as carboplatin or 254-S (20)(21)(22). It is very difficult to discuss the correlation between pharmacokinetic parameters and the pretreatment Ccr in this study, because the number of patients tested was very small (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this might be the decreased creatinine clearance and pretreatment with cisplatin (Reece et al, 1986;Mulder et al, 1988).…”
Section: Discussionmentioning
confidence: 99%